The Rate of Availability of Snakehead Fish Production in Banyuasin Regency and Ogan Ilir Regency - Puri Pratami Ardina Ningrum; Sisvaberti Afriyatna; Harniatun Iswarini; Novi Apriani; Rahmat Kurniawan; Mifdalatun Nisa (Universitas Muhammadiyah Palembang, 2026)
This study aims to analyze the availability of snakehead fish (Channa striata) at the Jakabaring Main Market in Palembang City, South Sumatra Province, based on social and economic aspects. The method used is descriptive quantitative with time series data for 2025 sourced from primary data. The results show that the availability of snakehead fish tends to fluctuate, but still follows a seasonal pattern. A decrease in supply occurs from May to June, indicating a period of scarcity, while a significant increase occurs at the end of the year, especially in December. From a social aspect, trader characteristics such as age, experience, and supplier networks play an important role in maintaining supply sustainability. In addition, the consumption culture of the Palembang community, which uses snakehead fish as a main ingredient in traditional foods, also contributes to consistently high demand. From an economic aspect, fluctuations in availability have a direct impact on price changes, so that limited supply triggers price increases. Meanwhile, abundant stock suppresses prices in the market. Overall, the availability of snakehead fish at the Jakabring Main Market in Palembang City, South Sumatra Province, is still relatively able to meet market demand, despite a critical period in the middle of the year. This shows that socio-economic factors and natural conditions are interrelated in determining the stability of supply and price of snakehead fish in the market.